Winning the Global Game: A Strategy for Linking People and Profits - Rosensweig, Jeffrey A (New York The Free Press, 1998)
In the 21st century global economy, emerging nations will provide almost half of the potential customers for western goods and services, concludes international business expert Jeffrey A. Rosensweig. Drawing on extensive research, Rosensweig contends that firms with truly global strategies will profit from the untapped resources of emerging markets and at the same time improve the living standards of the world's poor. Dismissing the doomsday scenario that so-called Third World nations will continue to be mired in poverty, he argues persuasively that western executives must break out of the mindset that profitable ventures can only be found within the "Triad" of the United States, Europe, and Japan.
Age Group: Adult
9. People and Profits: A Win-Win Global Strategy for the 21st Century.
Introduction: Globalization or "Globaloney"? -- Pt. I. Regional Aspects of (or Routes to) A Globalizing Economy. 1. The Limited World of Business at the End of the 20th Century (Traditional Triad). 2. Business Strategy into the 21st Century: Extending the Triad. 3. The Populous South: Will Markets for Growth or a Tragic Human Trap Emerge? 4. The Challenge of Development: Ending the South's Vicious Spiral -- Pt. II. The Potential of More Global Economic Progress. 5. Tomorrow's Customers: The Middle Class Goes Global (Divergent Economic Growth). 6. Strategic Focus: The Six Great Economies of the 21st Century -- Pt. III. A Global Strategy for People and Profits in the 21st Century. 7. Preparing for the Global Century: The Rationale, Route, and Tools for Diversifying Beyond the U.S. Market. A. Time-Phased Global Strategy for Business Expansion. B. Personal Global Investing Strategies. 8. 21st Century Career Strategy: Becoming a Global Manager.
Includes bibliographical references (p. 237-245) and index.
Keywords: International business enterprises; Management; Economic forecasting; Forecasting